The role of staple fiber length on the performance of carded, hydroentangled nonwovens produced with splittable fibers. (March 2019) - Tabor, Jordan; Wust, Carl; Pourdeyhimi, Behnam
Carding is a common web-forming process used for staple fibers in the nonwovens industry. Carded webs can be produced with bicomponent staple fibers designed to split into fine fibers. Splittable bicomponent fibers offer benefits such as increased surface area, improved hand, decreased pore size, improved cover, and enhanced strength. Splittable bicomponent fibers within carded webs can be split and bonded utilizing high-pressure water jets during the hydroentangling process. Staple fibers may be produced in many different lengths. However, the effect of staple fiber length on the nonwoven carding process and structure–property relationships of carded, hydroentangled nonwoven fabrics composed of splittable bicomponent fibers is not well understood. During this research, polyester/polyethylene 16-segmented pie, bicomponent fibers with lengths ranging from 2.54 to 15.24 cm were produced, carded and bonded by hydroentangling. All fiber lengths used during this research were successfully carded, and no significant challenges were observed during carding. Fabric performance was evaluated with air permeability and burst strength testing. Data sets were statistically evaluated with one-way and two-way analysis of variance to determine whether fiber length significantly affected fabric structure and properties. In general, the solid volume fraction and air permeability of the samples were affected by fiber length. However, fiber length did not strongly affect the burst strength of hydroentangled fabrics.